Anticipatory Effects around Proposed Regulation: Evidence from Basel III - Hendricks, Bradley E.; Neilson, Jed J.; Shakespeare, Catherine; Williams, Christopher D. (The Accounting Review, 2023)
ABSTRACT Regulation is often proposed, developed, and finalized over a lengthy rule-making period prior to its adoption. We examine the period over which banking authorities discussed, adopted, and implemented Basel III to understand how firms respond to proposed regulation. We find evidence to suggest that affected banks not only lobbied rule-makers against it but also made strategic financial reporting changes and altered their business models in ways that reduced their exposure to the proposed rule prior to rule-makers finalizing the regulation. Further, our results indicate a sequential response, with banks responding through lobbying and strategic financial reporting prior to making business model changes. These findings highlight the interplay among firms’ financial reporting, business model, and political choices in response to proposed regulation and indicate that the appropriate date for an event study may be the regulation’s announcement date rather than its adoption or implementation dates. JEL Classifications: G14; G21; G28; M41; M48.